Production of IgG autoantibody requires expression of activation‐induced deaminase in early‐developing B cells in a mouse model of SLE. Issue 10 (19th August 2014) - Umiker, Benjamin R.; McDonald, Gabrielle; Larbi, Amma; Medina, Carlos O.; Hobeika, Elias; Reth, Michael; Imanishi‐Kari, Thereza
<x xml:space="preserve">Abstract</x> Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the presence of pathogenic IgG antinuclear antibodies. Pathogenic IgG autoantibody production requires B‐cell activation, leading to the production of activation‐induced deaminase (AID) and class switching of IgM genes to IgG. To understand how and when B cells are activated to produce these IgG autoantibodies, we studied cells from 564Igi, a mouse model of SLE. 564Igi mice develop a disease profile closely resembling that found in human SLE patients, including the presence of IgG antinucleic acid Abs. We have generated 564Igi mice that conditionally express an activation‐induced cytidine deaminase transgene (Aicdatg), either in all B cells or only in mature B cells. Here, we show that class‐switched pathogenic IgG autoantibodies were produced only in 564Igi mice in which AID was functional in early‐developing B cells, resulting in loss of tolerance. Furthermore, we show that the absence of AID in early‐developing B cells also results in increased production of self‐reactive IgM, indicating that AID, through somatic hypermutation, contributes to tolerance. Our results suggest that the pathophysiology of clinical SLE might also be dependent on AID expression in early‐developing B cells.